Keynote Address: Empirically Exploring Narrative Productions of Meaning in Public Life - Loseke, Donileen R. (Qualitative Sociology Review, 2013)
Because socially circulating stories are key vehicles producing shared meaning in globalized, mass-mediated, and heterogeneous social orders, it is important to understand how some stories – and only some stories – can be evaluated by large numbers of people as believable and important. How do stories achieve widespread cognitive and emotional persuasiveness? I argue that understanding narrative persuasiveness requires a cultural-level analysis examining relationships between story characteristics and two kinds of meaning: Symbolic codes which are systems of cognitive meaning and emotion codes which are systems of emotional meaning. Persuasiveness of narratives is achieved by using the most widely and deeply held meanings of these codes to build narrative scenes, characters, plots, and morals. I demonstrate my argument using the example of the codes embedded in the social problem story of “family violence,” and I conclude with some thoughts about how sociologists might approach the production of socially circulating stories as topics of qualitative research and why there are practical and theoretical reasons to do so. My central argument is that examining relationships between cultural systems of meaning and the characteristics of narratives is a route to understanding a key method of public persuasion in heterogeneous, mass-mediated social orders